Makna menjadi keluarga ‘teroris’ bagi keluarga tersangka terorisme Amrozi dan Ali Ghufron di Desa Tenggulun, Kecamatan Solokuro, Kabupaten Lamongan - Anis Ulfiyatun (Faculty of Social and Political Science, Universitas Airlangga, 2015)
In understanding terrorism, comprehensive perspective is strongly needed in order to explain terrorism activity in a boarder structure. The main purpose of this article is to understand the circumstances that were redefined by terrorism suspect's family about their existence in the society. Another objective of this research was also to prove the presumption of being a terrorist's family and their response of massive terrorism related reportage from media. This research uses qualitative method to comprehend value and socio-cultural context in many terrorism cases, considering terrorits's family position and situation after the bombing. Primary data were collected by in-depth interview with Amrozy and Ali Ghufron's family. The research shows that terrorist's family has redefined their identity as terrorist's family by saying